Review of deepfake detection methods - Seppälä, Sami (My University, 2026)
This bachelor's thesis reviews methods for detecting deepfake media, examining peer-reviewed literature published between 2020 and 2025. This review also briefly covers deepfake generation methods such as GANs, autoencoders, and diffusion models. Detection methods are grouped into twelve categories, including CNN-based classification and physiological signal analysis. While many methods score above 95% accuracy on standard benchmarks, they struggle when tested on data they were not trained on, and video compression makes detection even harder. Methods based on physiological signal measurement and identity features performed better in robustness testing. The review concludes with recommendations for future research priorities.

Tässä kandidaatintutkielmassa tarkastellaan deepfake-median tunnistamismenetelmiä vertaisarvioituun, vuosina 2020–2025 julkaistuun kirjallisuuteen perustuen. Katsauksessa käsitellään myös lyhyesti deepfake-sisällön luontimenetelmiä, kuten GAN-verkkoja, autoenkoodereita ja diffuusiomalleja. Tunnistamismenetelmät on jaoteltu kahteentoista kategoriaan, joihin kuuluvat muun muassa CNN-pohjainen luokittelu ja fysiologisten signaalien analyysi. Vaikka monet menetelmät saavuttavat yli 95 prosentin tarkkuuden vakioiduilla vertailuaineistoilla, niiden suorituskyky heikkenee merkittävästi testattaessa aiemmin tuntemattomalla aineistolla. Videokompressio vaikeuttaa tunnistamista entisestään. Fysiologisten signaalien mittaukseen ja identiteettipiirteisiin perustuvat menetelmät kestivät paremmin tunnistusta heikentäviä häiriötekijöitä. Tutkielma päättyy suosituksiin tulevaisuuden tutkimusprioriteeteiksi.
Keywords: machine learning; deep learning; artificial intelligence; neural networks (information technology); deepfakes; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|